(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article explores the influence of cultural and educational factors on the formation of poetic ornithonyms in Uzbek and English. Ornithonyms—names related to birds—reflect a nation’s cultural and national consciousness, traditions, connection with nature, and artistic imagery. A comparative analysis highlights the symbolic, emblematic, and aesthetic features of bird imagery in Uzbek and English poetry, emphasizing the importance of the cultural-educational context. The study finds that folk traditions, literary works, and cultural values have significantly shaped the development of ornithonyms.